From Kindergarten Through Second Grade, U.S. Children's Obesity Prevalence Grows Only During Summer Vacations. Issue 11 (November 2016) - von Hippel, Paul T.; Workman, Joseph
Abstract : Objective: To assess the relative importance of school and nonschool risk factors, this study estimated whether overweight and obesity prevalence grows faster during the school year or during summer vacation. Methods: In the Early Childhood Longitudinal Study, Kindergarten Class of 2010–11, a nationally representative complex random sample of 18, 170 U.S. children was followed from the fall of kindergarten in 2010 through the spring of second grade in 2013. Children's weight and heights were measured in schools each fall and spring. A multilevel growth model was used to estimate growth in mean BMI, overweight prevalence, and obesity prevalence during each summer and each school year. Results: From the fall of kindergarten to the spring of second grade, the prevalence of obesity increased from 8.9% to 11.5%, and the prevalence of overweight increased from 23.3% to 28.7%. All of the increase in prevalence occurred during the two summer vacations; no increase occurred during any of the three school years. Conclusions: The risk of obesity is higher when children are out of school than when they are in school.